An audit of best evidence topic reviews in the International Journal of Surgery. (May 2015) - Mabvuure, Nigel Tapiwa; Klimach, Stefan; Eisner, Mark; Rodrigues, Jeremy Neil
Abstract: Introduction: IJS launched best evidence topic reviews (BETs) in 2011, when the guidelines for conducting and reporting these reviews were published in the journal. Aims: (1) Audit the adherence of all published BETs in IJS to these guidelines. (2) Assess the reach and impact of BETs published in IJS. Methods: BETs published between 2011 and February 2014 were identified fromhttp://www.journal-surgery.net/ . Standards audited included: completeness of description of study attrition, and independent verification of searches. Other extracted data included: relevant subspecialty, duration between searches and publication, and between acceptance and publication. Each BET's number of citations (http://scholar.google.co.uk/ ), number of tweets (http://www.altmetric.com/ ) and number of Researchgate views (https://www.researchgate.net/ ) were recorded. Results: Thirty-four BETs were identified: the majority, 19 (56%), relating to upper gastrointestinal surgery and none to cardiothoracic, orthopaedic or paediatric surgery. Twenty-nine BETs (82%) fully described study attrition. Twenty-one (62%) had independently verified search results. The mean times from literature searching to publication and acceptance to publication were 38.5 weeks and 13 days respectively. There were a mean 40 (range 0–89) Researchgate views/article, mean 2 (range 0–7) citations/article and mean 0.36 (range 0–2) tweets/article. Conclusions: Adherence to BET guidelines has been variable. Authors are encouraged to adhere to journal guidelines and reviewers and editors to enforce them. BETs have received similar citation levels to other IJS articles. Means of increasing the visibility of published BETs such as social media sharing, conference presentation and deposition of abstracts in public repositories should be explored. More work is required to encourage more submissions from other surgical subspecialties other than gastrointestinal specialties. Highlights: IJS has published best evidence topic reviews (BETs) since 2011. Adherence to the journal's BET guidelines is unknown. Adherence to guidelines has, mostly, been good. The quantity of citations to BETs is comparable to that of non-BET IJS articles.